Differences Between Mothers' and Fathers' Ratings of Family Functioning With the Family Assessment Device: The Validity of Combined Parent Scores. (July 2015) - Cooke, Dawson; Marais, Ida; Cavanagh, Robert; Kendall, Garth; Priddis, Lynn
The psychometric properties of the General Functioning subscale of the McMaster Family Assessment Device were examined using the Rasch Model ( N = 237 couples). Mothers' and fathers' ratings of the General Functioning subscale of the McMaster Family Assessment Device are recommended, provided these are analyzed separately. More than a quarter of couples differed significantly in their ratings.